The Effect of Implementing Medical Play on Anxiety Levels Due to Hospitalization in Preschool Children - Andriastuti, Anes; Lestari, Nur Eni; Purnamasari, Eka Rokhmiati Wahyu (Poltekkes Kemenkes Semarang, 2025)
Introduction : Preschool age is susceptible to various diseases, so it is not uncommon to require hospital care and experience hospitalization. One therapy that can help reduce the impact of hospitalization on children is play therapy (medical play).Objective : To analyze the effect of implementing medical play on the level of anxiety due to hospitalization in preschool children in the child care room.Method : This study used a quasi-experimental method with a one-group pretest-posttest design . The sampling technique was purposive sampling , with a sample size of 30 respondents. Data analysis was performed using the Marginal Homogeneity test.Results : The results of the study showed that the analysis of the effect of implementing medical play on the level of anxiety due to hospitalization in preschool children obtained a p-value of 0.00 (p 0.05).Conclusion : There is a significant effect of the application of medical play on the level of anxiety in children during hospitalization. The results of this study are expected to be a reference for hospitals, especially in the application of the concept of atraumatic care , by utilizing play therapy as an effective alternative to reduce children's anxiety during treatment.